Sharing the land, sharing a future - Graham, Katherine M.; Newhouse, David Locke 1973- (University of Manitoba Press, 2021)
"Sharing the Land, Sharing a Future looks to both the past and the future as it examines the foundational work of the Royal Commission on Aboriginal Peoples (RCAP) and the legacy of its 1996 report. It assesses the Commission's influence on subsequent milestones in Indigenous-Canada relations and considers our prospects for a constructive future. RCAP's five-year examination of the relationships of First Nations, Metis, and Inuit peoples to Canada and to non-Indigenous Canadians resulted in a new vision for Canada and provided 440 specific recommendations, many of which informed the subsequent work of the Truth and Reconciliation Commission of Canada (TRC). Considered too radical and difficult to implement, RCAP's recommendations were largely ignored, but the TRC reiterates that longstanding inequalities and imbalances in Canada's relationship with Indigenous peoples remain and quite literally calls us to action. With reflections on RCAP's legacy by its co-chairs, leaders of national Indigenous organizations and the Minister of Indigenous Crown Relations, and leading academics and activists, this collection refocuses our attention on the groundbreaking work already performed by RCAP. Organized thematically, it explores avenues by which we may establish a new relationship, build healthy and powerful communities, engage citizens, and move to action."--
Selected revised papers presented at a conference, the Royal Commission on Aboriginal Peoples Forum, "Hear Our Voice", in November, 2016, held in Winnipeg
Keywords: Kanada -- Commission on Aboriginal Peoples; Indigenes Volk; Eskimo; Métis; Soziale Ungleichheit; Kanada; Canada / Royal Commission on Aboriginal Peoples / Congresses; Indigenous peoples / Canada / Social conditions / Congresses; Indigenous peoples / Canada / Government relations / Congresses; Canada / Race relations / Congresses; Canada / Ethnic relations / Congresses; Native peoples / Canada / Government relations; HISTORY / Canada / Post-Confederation (1867-); POLITICAL SCIENCE.; SOCIAL SCIENCE / Ethnic Studies / Native American Studies; Canada / Royal Commission on Aboriginal Peoples; Ethnic relations; Indigenous peoples / Social conditions; Race relations; Canada; History / Canada - Post Confederation (1867-); Konferenzschrift